THE IMPACT OF PHYSICAL EDUCATION AND SPORTS CURRICULUM ON THE DEVELOPMENT OF LIFE SKILLS AMONG SENIOR HIGH SCHOOL STUDENTS IN TIMOR-LESTE. - Suri, Epifania Tilman (ASEAN Journal of Sport for Development and Peace, 2024)
This study aims to assess the efficacy of the existing physical education and sports curriculum on the development of life among senior high school students in Timor-Leste. The instrument used for this study is the Life Skill Scale Sport (LSSS) by Cronin Alen (2016). The collected data are analyzed using descriptive statistics within a survey design. The study encompasses a population of 203 senior high school students, comprising 97 males and 103 females, drawn from various schools in three municipalities. The findings of this study showed that the mean values of each factor seem to “strongly agree” which means there is the effectiveness of physical education and sports curriculum in developing life skills among senior high school students. Life skills for the students that have been learning through physical education and sport subject such as leadership, teamwork, and collaboration are essential for student’s personal growth and future career success, these skills enable students to lead effectively, work well to contribute to the collective goals.